The Effect of Baytril against Salmonella london Infection in Chickens: Z. A. Al-Chalabi , A. Abdul-Aziz and N. R. Mahdi - Al-Chalabi, Z. A. (The Iraqi Journal of Veterinary Medicine, 2005)
The purpose of this study was to obtain additional information regardingthe effectiveness of Enrofloxacin (Baytril®) against artificially inducedinfection of S. london in chickens.One hundred and sixty one day old chicks of mixed sex were dividedequally into two groups A (treated group) and B (control, infected non-treatedgroup). Chicks were reared on separated rooms on wood shavings litter, andgiven water and irradiated feed continuously for 55 days. All chickens wereinfected at 3 days with 4×105 S. london/ml in drinking water. The administrationof salmonella was followed by intestinal colonization, detected by isolation ofsalmonella from cloacal swabs, caecal contents and quantitative numeration pergrams of caecal contents, weekly for 8 weeks.Group A was treated with Enrofloxacin (Baytril®) 0.5 ml/L drinking wateron day 45 for 5 days. Twelve days after the end of the therapy the presence ofsalmonella could not be detected by cloacal swabs and in caecal contents.This suggests that Baytril seems to have a good efficiency in totalelimination of salmonella from the intestine of infected chickens.